Fe(III)-DOTA/Fe(III)-NOTA Complexes: Attractive Alternative Markers for Future Electrochemical Biosensors. Issue 11 (30th June 2020) - Gaillard, Michel; Kanso, Hussein; Denat, Franck; Calas-Blanchard, Carole; Inguimbert, Nicolas; Noguer, Thierry
Abstract : Metallic complexes of macrocycles chelators 1, 4, 7-triazacyclononane-N, N, N-triacetic acid (NOTA) and 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA) were synthetized with iron (III) giving Fe(III)-DOTA and Fe(III)-NOTA complexes. They were studied in comparison of ferricyanide and ferrocenemethanol on cyclic voltammetry with glassy carbon working electrode (GC) and screen-printed carbon electrode (SPCE). Diffusion coefficients and heterogeneous electron transfer rate constants were determined with Randles-Sevcik and Nicholson-Lavagnini methods. Using SPCE. The average values of diffusion coefficient and transfer rate constant were respectively of 1.34 × 10 −6 cm 2 s −1 and 1.01 × 10 −3 cm s −1 for Fe(III)-DOTA, and 4.32 × 10 −6 cm 2 s −1 and 1.14 × 10 −3 cm s −1 for Fe(III)-NOTA. Interestingly, characteristics of the synthetized complexes on SPCE compete advantageously with those of ferricyanide and ferrocenemethanol, making Fe(III)-DOTA and Fe(III)-NOTA potential markers for future biosensors development.